Disparities in Physical and Psychological Symptoms in Hospitalized African American and White Persons with Dementia. (June 2021) - Boltz, Marie; BeLue, Rhonda; Resnick, Barbara; Kuzmik, Ashley; Galik, Elizabeth; Jones, Joanne R.; Arendacs, Rachel; Sinvani, Liron; Mogle, Jacqueline; Galvin, James E.
Objectives: This study examined differences in physical function, delirium, depressive symptoms, and behavioral and psychological symptoms of dementia (BPSD) in hospitalized African American and white older adults with dementia.Methods: This secondary data analysis using baseline data from an ongoing trial testing family-centered function-focused care included African American ( n = 159) and white persons ( n =135) with dementia.Results: A multivariate analysis of covariance showed that controlling for relevant demographic and health characteristics, African Americans with dementia had lower physical function, more delirium, and more depressive symptoms upon admission than white participants. There were no significant differences in BPSD between African American and white persons.Discussion: To our knowledge, this is the first study to examine racial differences in admission symptoms of hospitalized persons with dementia. While the findings are preliminary, they can be used to inform the design of future research, including identifying the causes of disparities.